2015
DOI: 10.1007/978-3-662-45657-6_25
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium on the Morphology of Rhizopus oryzae and L-lactic Acid Production

Abstract: The effects of exogenous calcium on fungal pellet morphology during preculture and L-lactic acid production were studied. The results showed that addition of exogenous calcium could induce pellet formation. The diameter of the pellet increased with increasing concentration of exogenous calcium, including CaCl 2 and CaCO 3 . The smaller pellet precultured with low concentration of soluble calcium (CaCl 2 ) was beneficial for L-lactic acid production because the pellet was dense and the large inner part of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, the removal of biomass after incubation will be easier when the pellet morphology is used [2,10]. Previous studies showed that the fungal pellet diameter was connected with the fermentation performance, and the highest yield was obtained when using pellets of smaller diameter, which may be interpreted that the inner zone of larger pellets was relatively inactive [4], limiting internal mass transfer [17]. On the other hand, the smaller pellet had an increased surface area, which can contact with more substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the removal of biomass after incubation will be easier when the pellet morphology is used [2,10]. Previous studies showed that the fungal pellet diameter was connected with the fermentation performance, and the highest yield was obtained when using pellets of smaller diameter, which may be interpreted that the inner zone of larger pellets was relatively inactive [4], limiting internal mass transfer [17]. On the other hand, the smaller pellet had an increased surface area, which can contact with more substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology is influenced by the strain characteristics as well as the medium composition and cultivation conditions [12][13][14][15]. Growth in pellet form has been reported as a favourable alternative for fungal cultivation, because it enables repeated-batch fermentation and improves the rheology of the broth, resulting in better mass and oxygen transfer in the reactor with lower energy consumption [12][13][14][15]. Morphology of the fungi can affect the production of primary and secondary metabolites [16].…”
Section: Introductionmentioning
confidence: 99%